The Tourism Promotion Training at PT PRPP Central Java - Syaefudin, Mohamad; Adawiyah, Aisyiah Al (Universitas Negeri Semarang, 2023)
The potential of edutaintment PT PRPP Central Java needs to be developed following the times. The arrangement of tourist spots, events and promotiaons is still being improved by management. The rebranding of PT PRPP was also carried out in order to be able to target the melenials so that they could travel to get to know the cultural diversity of Central Java. The addition of instagrammable spots and creating events for young people is needed. To increase tourism promotion on target for the melenial generation, this service is carried out. The goal is for partners to get support in increasing promotions among millennials. The long-term goal is to increase income for management from visits. This service is carried out by training the making of tourism promotional videos so that they are better known to tourists.